2020
DOI: 10.3390/cells9061368
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor-1 and IGF Binding Proteins Predict All-Cause Mortality and Morbidity in Older Adults

Abstract: While the growth hormone/insulin-like growth factor-1 (GH/IGF-1) pathway plays essential roles in growth and development, diminished signaling via this pathway in model organisms extends lifespan and health-span. In humans, circulating IGF-1 and IGF-binding proteins 3 and 1 (IGFBP-3 and 1), surrogate measures of GH/IGF-1 system activity, have not been consistently associated with morbidity and mortality. In a prospective cohort of independently-living older adults (n = 840, mean age 76.1 ± 6.8 years, 54.5% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 101 publications
(156 reference statements)
0
31
0
1
Order By: Relevance
“…A decrease in growth hormone and oxytocin levels with age, on the one hand, is associated with a general slowdown in growth and development of all body systems, including regeneration processes. On the other hand, due to an increase of the IGF-1/IGFBP-3 ratio, this stimulates the predominance of high mTOR-dependent metabolic activity and insulin resistance [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in growth hormone and oxytocin levels with age, on the one hand, is associated with a general slowdown in growth and development of all body systems, including regeneration processes. On the other hand, due to an increase of the IGF-1/IGFBP-3 ratio, this stimulates the predominance of high mTOR-dependent metabolic activity and insulin resistance [ 150 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blood level of IGF-1 reaches its maximum during adolescence and then gradually declines [ 149 ]. At the same time, the increased IGF-1/IGFBP-3 molar ratio in serum of the elderly is positively associated with the all-cause morbidity and mortality, including cancer, diabetes, cardiovascular and cognitive disorders, while the IGFBP-3 level itself is negatively associated with the all-cause mortality [ 150 ].…”
Section: Circulating Hormones and Growth Factors Associated With Amentioning
confidence: 99%
“…By contrast, epidemiological studies of the naturally occurring variation in circulating IGF-1 have shown null or mixed results (Milman et al, 2016). Some studies, including those from our longevity cohorts, have shown a positive association between high IGF-1 and adverse outcomes (Milman et al, 2014;Spoel et al, 2015;Zhang et al, 2020). Others, often from somewhat younger populations, have shown the opposite: higher IGF-1 being associated with protection from disease and death (Bourron et al, 2015;Friedrich et al, 2009).…”
Section: The Role Of Igf-1 In Agingmentioning
confidence: 95%
“…In addition to insulin or GH, the production and secretion of IGF-1 are also influenced by other hormones, e.g., sex hormones [ 87 ], as well as factors such as age [ 19 , 88 ], sex, diet and nutrition [ 89 ], circadian rythm [ 90 ], and microbiota-derived metabolites [ 91 ]. Genetic defects with potential to affect both GH secretion and IGF-1 bioavailability and action are also a subject of a recent review [ 92 ].…”
Section: Igf System Components and Signalingmentioning
confidence: 99%